Approach Phytochemistry of Secondary Metabolites of Maytenus Guianensis Klotzsch ex Reissek (Celastraceae) - Lima, Renato Abreu; Hurtado, Fernanda Bay; Meneguetti, Dionatas Ulisses; Facundo, João Bezerra; Militão, Júlio Sancho; Facundo, Valdir Alves (Ciência e Natura, 2016)
The Brazilian Amazon rainforest, even for its richness and biological diversity, can offer the oppotunity for innovative and efficient discovery of molecules with potential use in large scale. The interest in secondary metabolites have grown tremendously in recent amazonian essential oils and plant extracts, the Maytenus guianensis is a shrub native to our region, being popularly known as fruit-werewolf. The leaves are used as anti-inflammatory and infections is also indicated in the treatment of arthritis and hemorrhoids. Thus, the present study aimed to identify the classes of secondary metabolites from the ethanol extract of the fruits, leaves and shell of M. guianensis. We carried out the identification of secondary metabolites with plant extract using specific reagents alkaloids, glycosides cardiotonic, coumarins, flavonoids, tannins, saponins and triterpenes, based on coloration and precipitation. It was found that all the studied structures show botanical alkaloids, coumarins, flavonoids and tannins using any specific reagents. However, the absence of a secondary metabolite which can serve as raw material for synthesis of bioactive substances, particularly drugs and are used in many preparations to benefit human health, such as in the production of food and biological activity against microrganisms.